Obstetric Outcome After Surgical Treatment of Endometriosis: A Review of the Literature - Mooney, Samantha S.; Ross, Vanessa; Stern, Catharyn; Rogers, Peter A. W.; Healey, Martin (Frontiers in Reproductive Health, 2021)
A diagnosis of endometriosis is associated with increased risks of adverse pregnancy outcomes including placenta praevia and preterm birth. Some studies have also suggested associations with gestational hypertension, fetal growth restriction, gestational diabetes, perinatal death, and obstetric haemorrhage. This review aims to assess the impact of pre-pregnancy surgical treatment of endometriosis on future obstetric outcomes. A search of the Medline, Embase and PubMed electronic databases was performed to identify studies reporting pre-pregnancy surgery for endometriosis and subsequent pregnancy outcome compared to controls with unresected endometriosis. Three studies met the inclusion criteria. The studies were heterogenous in design, definition of study groups and outcome measures. All three studies were judged at critical risk of bias. Pre-pregnancy excision of endometriosis was associated with an increased risk of caesarean section in one of two studies, OR 1.72 (95% CI 1.59-1.86) and OR 1.79 (95% CI 0.69-4.64). Placenta praevia rates were also increased in one of two studies OR 2.83 (95% CI 0.56-12.31) and OR 2.04 (95% CI 1.66-2.52). One study found increased risks of preterm birth, small for gestational age, gestational hypertension, and antepartum and postpartum haemorrhage (all p<0.05) with pre-pregnancy excision of endometriosis. There is insufficient evidence examining the role of pre-pregnancy endometriosis surgery in ameliorating adverse pregnancy outcomes, and thus reliable conclusions cannot be drawn. Prospectively designed studies are needed to assess the relationship between surgical treatments for endometriosis and obstetric outcome and examine potential confounders such as comorbid adenomyosis and infertility.